Effects of career readiness module on career self-efficacy among university students - Nik Rafidah Nik Yusoff; Mastura Mahfar; Muhammad Sukri Saud; Aslan Amat Senin (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aimed to identify the effects of the Career Readiness Module on career self-efficacy and its subscales, namely self-appraisal, occupational information, goal selection, planning and problem solving among university students. The randomized pretest-posttest control group were used in this study. A total of 60 second year students from the School of Computing, Faculty of Engineering, Universiti Teknologi Malaysia, were selected as research subjects using random cluster sampling. Both groups completed the Career Decision Self-Efficacy–Short Form (CDSE-SF) and the Big Five Inventory (BFI) questionnaires before and after the two-month intervention sessions. Data were analyzed using Statistical Package for Social Science version 23.0. The repeated-measures ANOVA and effect size were used to test the hypotheses of study. The study results showed significant differences in the experimental group for career self-efficacy and each of its subscale between pre-test, post-test 1, and post-test 2 at the p≤.05 significant level. This study also demonstrated the significance of implementing the Career Readiness Module among university students prior to graduation in order to improve their career self-efficacy.